THE ROLE OF INNOVATIVE METHODS IN THE FORMATION OF PROFESSIONAL COMPETENCES OF A FUTURE TEACHER - Karimova Fotima Abdukakhkharovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article examines the role of innovative methods in the formation of professional competencies of a future teacher. Innovative teaching methods also include gaming technologies. World pedagogy has accumulated significant experience in using games in the educational process. Games are the most important means of mental and moral education. With the help of gaming technologies, a teacher can simultaneously give students theoretical and practical knowledge.